2020
DOI: 10.1039/c9cc09709k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of difluoromethyl and deuterium-labeled difluoromethyl thioethers from aliphatic electrophiles

Abstract: A one-pot difluoromethylthiolation of alkyl electrophiles with thiourea and diethyl bromodifluoromethylphosphonate is described. By changing the “H” source to most commonly used “D” source CD3OD and D2O, this strategy enables efficient synthesis of SCF2D-substituted molecules in good yields with high levels of D incorporation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Firstly, we investigated 4-chlorophenylacetic acid, 4-phenylphenylacetic acid, 4'-methoxy-biphenyl-4-acetic acid, 2-naphthylacetic acid and 2-methyl-2-(p-tolyl) propanoic acid, the corresponding products (23)(24)(25)(26)(27) were obtained in good yields. After that, 2-(3,5-dichlorophenoxy) acetic acid, 2,3-dihydrobenzo[b] [1,4] dioxine-2-carboxylic acid, 2-phenylcyclopropane-1-carboxylic acid, 2-oxo-2phenylacetic acid were examined as well under the standard conditions, the corresponding target products (28)(29)(30)(31) were rendered in moderate to good yields (46-73%). Our system was also compatible with pure aliphatic carboxylic acids, which had been well demonstrated by the products 32-37.…”
Section: Substrate Scopementioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, we investigated 4-chlorophenylacetic acid, 4-phenylphenylacetic acid, 4'-methoxy-biphenyl-4-acetic acid, 2-naphthylacetic acid and 2-methyl-2-(p-tolyl) propanoic acid, the corresponding products (23)(24)(25)(26)(27) were obtained in good yields. After that, 2-(3,5-dichlorophenoxy) acetic acid, 2,3-dihydrobenzo[b] [1,4] dioxine-2-carboxylic acid, 2-phenylcyclopropane-1-carboxylic acid, 2-oxo-2phenylacetic acid were examined as well under the standard conditions, the corresponding target products (28)(29)(30)(31) were rendered in moderate to good yields (46-73%). Our system was also compatible with pure aliphatic carboxylic acids, which had been well demonstrated by the products 32-37.…”
Section: Substrate Scopementioning
confidence: 99%
“…Subsequently, Ngai et al reported a distinct radical approach for catalytic C-H difluoromethoxylation of (hetero)arenes using difluoromethoxylative reagents [11][12] (Figure 1B, left). Of note, as an important and special fluorine-containing intermediate in organic synthesis [13][14][15][16][17][18][19][20][21][22][23][24] , difluorocarbene has been combined with various alcohols or thiolsto synthesize difluoromethyl ethers [25][26][27][28] or thioethers [29][30] (Figure 1B, right). Despite the progress achieved in recent years on the synthesis of difluoromethyl ethers, their efficient synthetic methods are still rare and the development of a general and practical strategy for their construction is still highly appealing, especially in terms of complexity and versatility of difluoromethoxy compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, Billard’s group successfully synthesized the molecule with SCF 2 D through a two-step synthesis (Figure c) . In 2020, Yi’s group reported a mild and transition-metal-free method for the one-pot preparation of deuterated difluoromethyl thioethers in high yield with a high deuterium incorporation level (Figure d) . Colby’s group synthesized ketones and sulfones with CF 2 D by releasing trifluoroacetate from highly fluorinated gem glycol (Figure e) .…”
mentioning
confidence: 99%
“…8 In 2020, Yi's group reported a mild and transition-metal-free method for the onepot preparation of deuterated difluoromethyl thioethers in high yield with a high deuterium incorporation level (Figure 1d). 9 Colby's group synthesized ketones and sulfones with CF 2 D by releasing trifluoroacetate from highly fluorinated gem glycol (Figure 1e). 10 In 2020, Jamison's group reported the use of the continuous-flow method to produce deuteriodifluoromethylated products by reacting chlorodifluoromethane gas with aldehydes in high yields with a high deuterium incorporation level (Figure 1f).…”
mentioning
confidence: 99%
“…Two strategies for HCF 2 Se and HCF 2 S installation have been well established, difluoromethylation of selenium or sulfur-containing compounds and direct difluoromethyl­selenolation or difluoromethyl­thiolation . Direct difluoromethyl­selenolation is highly efficient, but only two reagents have been developed, HCF 2 SeCl and TsSeCF 2 H (Scheme , eq a).…”
mentioning
confidence: 99%